Brooklyn, New York foodscape 2007–2011: a five-year analysis of stability in food retail environments - Filomena, Susan (BioMed Central, 2013)
BACKGROUND: Food retail studies have focused on the availability of food stores, and on disparities in food access by neighborhood race and income level. Previous research does not address possible changes in local food environments over time, because little is known about the extent to which food environments fluctuate. METHODS: Records of stores licensed to sell food with the New York State Department of Agriculture and Markets from 2007–2011 were compared to detect differences in the total number of food stores and supermarkets annually, as well as the total change for the five-year period. Food stores and supermarkets per 10,000 persons were also calculated. Food retail stability – how many individual food stores opened and closed – was also calculated for total stores and supermarkets. All results were stratified by income level and racial characteristics of 2000 Census Bureau census tracts. RESULTS: There was an overall increase in all food stores, as well as in supermarkets specifically. However, stability – the proportion of stores that remained open for five years – was greater in higher-wealth and predominantly white areas. Supermarkets remained open in greater proportion than total stores in all racial/ethnic and income areas, but areas with the highest wealth had the greatest supermarket stability. Those areas also had slightly more supermarkets per 10,000 persons, and had no permanent closures of supermarkets. The proportion of new store locations was similar between areas, but lowest-income areas had the greatest proportion of new supermarket locations. CONCLUSIONS: These data suggest that food retail environments change over short periods of time. Stability of food retail environments varies between neighborhoods by race and income. Fluctuations may need to be studied further to understand their impact on food behaviors and health of residents. Finally, the dynamic nature of food retail environments suggests opportunities for policymakers and community organizations to create programs that promote the availability of healthier foods at the neighborhood level.